Effect of Cement Pollution on Serum Creatinine and Blood Urea in Cement Factory Workers (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Cement dust is one of the major air pollutants and its exposure causes multiple health hazards. It can invade human body through different routes and enter into systemic circulation which affects microstructure of different organ like liver, lung and kidney. Aim of this study was to assess the effect of cement pollution onserum creatinine and blood urea in cement factory workers of Chattogram City. Materials and methods: This was ananalytical (Comparative) cross-sectional studyconducted from July 2022 to June 2023 in the Department of Physiology, Chittagong Medical College, Chattogram. Total 76 male subjects aged between 20 50 years were included in this study by simple random sampling. 38 workers of selected cement factory in Chattogram who were directly exposed to cement dust and another age and BMI matched apparently healthy 38 subjects who were not directly exposed to cement dust in their working environment were enrolled in this study. Serum creatinine and blood urea were assessed for kidney function. Unpaired student’s t-test and Pearson’s correlation coefficienttest were done for statistical analysis. Results: Mean value of serum creatinine was significantly higher in cement dust exposed group in comparison to unexposed group (p0.05). No significant changes were observed in serum creatinine and blood urea regarding duration of exposure to cement dust. There were no significant correlation between serum creatinine and blood urea with duration of job exposure (p>0.05). Conclusion: The result of this study concludes that exposure to cement dust significantly alter serum creatinine level.Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 86-90